Regency of birth as marker of future fertility: empirical investigation with programme implications - Srinivasan, K.; Alagararajan, M. (2003)
The persistence of high growth rates of the population in a number of states is calling to question the wisdom and feasibility of integrating family planning programmes in a larger reproductive health package as recommended in the National Population Policy 2000. There is an apparent inconsistency between the needs of the state governments to regulate population growth and fertility levels as part of development strategies and the requirements for implementation of family planning programmes as a part of a larger reproductive health package. In this article an attempt is made to reconcile this inconsistency through a birth-based approach to contraception which is feasible, humane and effective in terms of its fertility impact. The data from NFHS-2 are used to empirically validate the approach. - Reproduced.
Keywords: Fertility; Population; Birth control; Family planning